Structural Peculiarities of Coal Mine Waste Piles in Kuzbass; Journal of Mining Science; Vol. 53, iss. 1 - Prokopenko S. A. Sergey Arturovich; Ludzish V. S. Vladimir Stanislavovich; Lesin Yu. V. Yury Vasiljevich; Tyulenev M. A. Maksim Anatoljevich; Sushko A. V. Anastasiya Viktorovna (2017, 2017)
Title screen